രണ്ടു ജീവിതങ്ങൾ / Two lives, - Seth, Vikram (DC Books, 2011)
"Shanti Behari Seth was born on the eighth day of the eighth month in the eighth year of the twentieth century; he died two years before its close. He was brought up in India in the late years of the Raj, and was sent by his family in the 1930s to Berlin - though he could not speak a word of German - to study medicine and dentistry. It was here, before he migrated to Britain, that Shanti's path first crossed that of his future wife." "Henny Gerda Caro was also born in 1908, in Berlin, to a Jewish family, cultured, patriotic and intensely German. When the family decided to have Shanti as a lodger, Henny's first reaction was, 'Don't take the black man!' But a friendship flowered, and when Henny fled Hitler's Germany for England, just one month before war broke out, she was met at Victoria Station by the only person she knew in the country: Shanti." "Vikram Seth has woven together their astonishing story: the war that took Shanti to North Africa, the Middle East and the battle of Monte Cassino, where his right arm was blown off; the persecution that saw Henny desperately searching for news of the mother and sister she had left behind; the love that sparked their marriage in 1951; the courage that inspired Shanti to defy his injury and set up once again in his profession; the arrival into this childless couple's lives of their great-nephew from India, the teenage student Vikram Seth. The result is a tapestry of India, the Third Reich and the Second World War, Auschwitz, and the Holocaust, Israel and Palestine, post-war Germany and 1970s Britain. Two Lives is both a history of a violent century seen through the eyes of two survivors as well as an intimate portrait of their friendship, marriage and abiding yet complex love. Part biography, part memoir, part meditation on our times, this is the true tale of two remarkable lives."--BOOK JACKET.